2020
DOI: 10.20944/preprints202005.0269.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence, Pattern and Outcome of Pediatric Lassa Fever Disease (LFD) in a Tertiary Hospital, Southeast Nigeria

Abstract: The prevalence and case fatality rates of Pediatric Lassa fever disease (LFD) are not well documented. This study was aimed at determining the prevalence, pattern and outcome of Pediatric LFD. It was a prospective observational study. A total of 183 subjects that met the criteria for LFD suspects were recruited consecutively and subjected to Lassa virus PCR test. Structured questionnaire was used to collect information. Of the 183 children recruited, 24 tested positive to Lassa virus PCR, giving a positivity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
1
1
Order By: Relevance
“…However, in contrast to previous reports, we found a higher proportion of our cohort to be male. 14 , 26 As with previous descriptions of pediatric LF, cough, vomiting, headache, low oxygen saturation, and temperature ≥ 38°C were common initial clinical presentations in our cohort. 2 , 14 , 19 Most of these symptoms have been described by the WHO as minor criteria for LF and in some studies as typical of “early presentation” with a good clinical prognosis when treatment with ribavirin is started early.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, in contrast to previous reports, we found a higher proportion of our cohort to be male. 14 , 26 As with previous descriptions of pediatric LF, cough, vomiting, headache, low oxygen saturation, and temperature ≥ 38°C were common initial clinical presentations in our cohort. 2 , 14 , 19 Most of these symptoms have been described by the WHO as minor criteria for LF and in some studies as typical of “early presentation” with a good clinical prognosis when treatment with ribavirin is started early.…”
Section: Discussionsupporting
confidence: 85%
“…We report a disease positivity rate of 19.5% (57/292) among children suspected of LF and a CFR of 63% (36/57) among our LF antigen–positive cohort. The CFR reported in our pediatric cohort is much higher than the CFR of 29.2% reported in a recent pediatric cohort from Ebonyi, Nigeria, 26 and higher than the overall CFR of 15% generally reported by the WHO for hospitalized patients with LF (both adult and children). 27 Although the prevalence and CFR for pediatric LF are still not well described, it has been reported that asymptomatic or mild disease represents approximately 80% of all LF infections.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation